Predicting the duration of supplemental home oxygen in prematurely-born infants at discharge from neonatal care. (June 2021) - Teoh, Sophia; Bhat, Ravindra; Greenough, Anne; Dassios, Theodore
Abstract: Background: Discharge home of preterm infants on supplemental oxygen has significant healthcare, parental psychological and financial implications, but the potential ability of clinical parameters at discharge to predict the duration of home oxygen has not been previously examined. Aims: To use clinical and epidemiological parameters available at discharge to predict the duration of home oxygen therapy. Study design: Retrospective observational cohort study with a primary and a validation cohort. Subjects: Seventy one infants born <32 completed weeks of gestational age, born between 1/1/2013–1/1/2020 at King's College Hospital NHS Foundation trust and discharged home on supplemental oxygen were studied. Outcome measure: Duration of home oxygen therapy. Results: In a primary cohort of 52 infants with a median (IQR) gestational age of 26.4 (25.0–28.1) weeks and birth weight of 0.81 (0.69–0.96) kg, the duration of home oxygen was four (3–7) months (range: 1–22 months). The postmenstrual age (adjusted p  = 0.001) and oxygen flow at discharge (adjusted p  = 0.046) were independently associated with the duration of home oxygen therapy. In a validation cohort of 19 infants, the correlation coefficient between the calculated and the observed duration of home oxygen was 0.62, p  = 0.005 and the coefficient of determination was 0.38. Conclusions: Infants discharged home on higher oxygen flows and at a greater postmenstrual age require a longer duration of home oxygen therapy and these parameters can be used to predict the duration of home oxygen therapy. Highlights: Home discharge of preterm infants on supplemental oxygen is associated with significant healthcare implications. We investigated if clinical parameters at discharge can predict the duration of supplemental home oxygen in preterm infants. Infants discharged home on higher oxygen flows and at a greater postmenstrual age require a longer duration of home oxygen. The oxygen flow and postmenstrual age at discharge can predict the duration of home oxygen therapy with moderate accuracy.